2016
DOI: 10.1158/1055-9965.epi-15-0983
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Human Papillomavirus Vaccination in a Large Clinical Population of Males Aged 11 to 26 years in Maryland, 2012–2013

Abstract: Background Despite the recommendation for routine human papillomavirus (HPV) vaccination in males, coverage estimates remain low. We sought to identify predictors of receiving each HPV vaccine dose among a large clinical population of males. Methods We conducted a cross-sectional analysis of electronic medical records for 14,688 males aged 11–26 years attending 26 outpatient clinics (January 2012 –April 2013) in Maryland to identify predictors of each HPV vaccine dose using multivariate logistic regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…HPV vaccination may offer racial and ethnic minority groups even greater potential for cancer reduction given their higher incidence of some HPV cancers. However, some studies suggest racial and ethnic disparities in HPV vaccine uptake (Chao et al, 2010;Wei et al, 2013), even as other studies suggest differences favor minorities (Clarke et al,2016;Reiter et al, 2013) or show no difference (Brewer et al, 2011;Hirth et al, 2014). We sought to comprehensively characterize differences between racial and ethnic minorities and Whites in HPV vaccine initiation and follow-through.…”
Section: Introductionmentioning
confidence: 99%
“…HPV vaccination may offer racial and ethnic minority groups even greater potential for cancer reduction given their higher incidence of some HPV cancers. However, some studies suggest racial and ethnic disparities in HPV vaccine uptake (Chao et al, 2010;Wei et al, 2013), even as other studies suggest differences favor minorities (Clarke et al,2016;Reiter et al, 2013) or show no difference (Brewer et al, 2011;Hirth et al, 2014). We sought to comprehensively characterize differences between racial and ethnic minorities and Whites in HPV vaccine initiation and follow-through.…”
Section: Introductionmentioning
confidence: 99%
“…We then found 13 factors that were categorized as sociodemographic factors and social structure factors, including age, sexual orientation, relationship or marital status, parental age, race or ethnicity, education level, employment status, nativity status, number of children in the household, parental education level, parental marital status, language proficiency of caregivers, and parental employment status. Approximately half of the studies (n=16) explored age as a factor related to the HPV vaccination initiation [ 17 , 18 , 30 , 34 , 36 , 38 , 40 , 43 , 46 - 49 , 51 , 54 , 55 , 57 ]. Among them, 9 studies showed significant associations between age and vaccination [ 17 , 30 , 36 , 38 , 40 , 46 , 47 , 51 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Approximately half of the studies (n=16) explored age as a factor related to the HPV vaccination initiation [ 17 , 18 , 30 , 34 , 36 , 38 , 40 , 43 , 46 - 49 , 51 , 54 , 55 , 57 ]. Among them, 9 studies showed significant associations between age and vaccination [ 17 , 30 , 36 , 38 , 40 , 46 , 47 , 51 , 55 ]. However, the 5 studies with teenagers reported more vaccinations at older ages [ 17 , 36 , 40 , 46 , 47 ], whereas the other 4 studies covering populations aged up to 26 years reported the opposite relationship [ 30 , 38 , 51 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations